Disinfection booth for people to reduce the transmission of COVID-19 in the community - Calderon, Maria (2020)
The COVID-19 pandemic has put the world’s governments in an unprecedented situation in which it is necessary to make quick decisions regarding the best strategies to reduce transmission. As part of these strategies, disinfection booths in the community are being implemented in many parts of the world. This document seeks to evaluate the effectiveness and safety of the disinfection booth for people to use in the community through an exhaustive search in the main bibliographic databases as well as in the main relevant institutions worldwide. After conducting the search, we found three technical documents in which the use of these technologies is not recommended because there is insufficient evidence and because they are of potential risk for people due to mucosal conditions. Another WHO recommendation document, although it does not specifically mention technology, mentions that the spraying of disinfecting substances should be avoided in people due to health risks. In conclusion, we found no scientific evidence to support the use of this technology.